Implementation of the integral model for the prevention of fraud and corruption, developed by the subdirection of audit and management of the risk of the administrative unit special agency of the general inspector of taxes, income and scientific contributions - ITRC (2017)
The phenomenon of corruption is a topic of worldwide interest today, people have become aware of the importance of attacking it and seek mechanisms to eradicate it. In Colombia, the constant news about embezzlements and fraudulent actions has led the Government to pay more attention in the analysis of the facts that needs to be modernized in the control models that they use, involving innovation aspects that allows to anticipate the consequences in the presence of corruption in order to prevent the devastating effects that such acts may cause.